2017
DOI: 10.1001/jamapsychiatry.2016.3644
|View full text |Cite|
|
Sign up to set email alerts
|

Repetitive Transcranial Magnetic Stimulation for the Acute Treatment of Major Depressive Episodes

Abstract: clinicaltrials.gov Identifier: PROSPERO CRD42015019855.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
325
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 415 publications
(357 citation statements)
references
References 110 publications
21
325
0
11
Order By: Relevance
“…28 Despite some mixed results (likely in part related to the issues described above), rTMS for medication-resistant depression has shown efficacy in larger trials and the FDA has cleared four different devices for this indication. 46 Furthermore, multiple studies have gone on to show real-world clinical effectiveness 47 and cost effectiveness. 48 Two companies (Nexstim and Neuronix) have recently completed pivotal, premarket approval studies for two new applications of rTMS, motor recovery in stroke rehabilitation 49 and cognitive improvement in Alzheimer’s disease.…”
Section: Implications Of Differential Placebo Effectsmentioning
confidence: 99%
“…28 Despite some mixed results (likely in part related to the issues described above), rTMS for medication-resistant depression has shown efficacy in larger trials and the FDA has cleared four different devices for this indication. 46 Furthermore, multiple studies have gone on to show real-world clinical effectiveness 47 and cost effectiveness. 48 Two companies (Nexstim and Neuronix) have recently completed pivotal, premarket approval studies for two new applications of rTMS, motor recovery in stroke rehabilitation 49 and cognitive improvement in Alzheimer’s disease.…”
Section: Implications Of Differential Placebo Effectsmentioning
confidence: 99%
“…Finally, while sham conditions have been used to demonstrate superiority of rTMS relative to placebo (for review, see Brunoni et al, 2017), research studies such ours typically do not include sham due to the ethical difficulties involved. Finally, while sham conditions have been used to demonstrate superiority of rTMS relative to placebo (for review, see Brunoni et al, 2017), research studies such ours typically do not include sham due to the ethical difficulties involved.…”
Section: Limitationsmentioning
confidence: 99%
“…In Japan, rTMS was approved as a novel therapy for treatment‐resistant depression in September 2017. Clinical trials and meta‐analyses have demonstrated the efficacy of facilitatory stimulation such as high‐frequency rTMS and intermittent theta burst stimulation (iTBS) over the left prefrontal cortex …”
Section: Introductionmentioning
confidence: 99%